Absolute nodal coordinate formulation for dynamic analysis of reinforced concrete structures. (October 2021) - Xiao, Han; Hedegaard, Brock D.
Abstract: An efficient and accurate beam element for performing explicit dynamic analysis of reinforced concrete beam elements was built using the absolute nodal coordinate formulation (ANCF). Such a formulation is useful for performing dynamic analysis under large strains and displacement with sudden load changes, such as during impact loading or for progressive collapse analysis. Compared with traditional nodal position formulations, ANCF uses position vector gradients to describe the rotation of the body and strain state, thereby avoiding the need for interpolating non-vectoral rotation parameters. The fiber element method was applied to calculate element stiffness from section deformations by subdividing beam elements into uniaxial fibers. The combined fiber element beam-column model with ANCF was validated by traditional co-rotational analysis and the quadrature element method (QEM), and thus may be used in general nonlinear dynamic analysis.